Medium-Term Exchange Rate Forecasting : What Can We Expect? - Meredith, Guy (IMF Working Papers; Working Paper ;, 2003)
The medium-term predictability of exchange rate movements is examined using three models of fundamentals: purchasing power parity, the monetary model, and uncovered interest parity. While the first two approaches yield favorable in-sample results, these largely reflect finite-sample estimation biases. Adjusting for these biases, there is little evidence of predictability, consistent with the lack of systematic improvement in out-of-sample forecasting performance relative to a random walk. Uncovered interest parity fares better at long horizons, but reflects information already embodied in market prices; in this sense, it may not be useful as an indicator of exchange rate misalignment. While more elaborate models of fundamentals might have better medium-term forecasting properties, careful attention must be paid to finite-sample biases in assessing predictability.